Let f(x) = (x+3)^3 + 2.

The graph of the inverse function y = f^–1(x) has a vertical tangent at:

(Hint: Think about the symmetry of the 2 graphs.)

(66, 1)
(2, –3)
(10, –1)
(–3, 2)
(–1, 10)

5 answers

clearly, since f'(-3) = 0, f^-1 has a vertical tangent at x = f^-1(-3) = 2.
Thank you. I was taking the inverse of (x+3)^3 + 2 and then I got stuck after that.
I wanted to let others who are looking for help know that the correct answer is (2,-3)
Thanks purple
Just plot the graph of inverse function, you would see (2,-3) is the correct answer.